ANALISIS ALTERASI DAN MINERALISASI BERDASARKAN PENGAMATAN MEGASKOPIK DAN MIKROSKOPIK PADA DAERAH PROSPEK X KABUPATEN BOLAANG MONGONDOW, SULAWESI UTARA: ALTERATION AND MINERALIZATION ANALYSIS BASED ON OBSERVATION OF MEGASCOPIC AND MICROSCOPIC ON PROSPECT "X" IN BOLAANG MONGONDOW REGENCY AT NORTH SULAWESI - Christi, Gita Dela; Sulistiyono, Sulistiyono; Handayani, Tatik; Widhiyatna, Denni (Buletin Sumber Daya Geologi, 2024)
The North Arm of Sulawesi Island is a gold-rich metallogenic belt. The study area is located in Bakan Village, Bolaang Mongondow Regency, North Sulawesi in the IUP area of PT J Resources Bolaang Mongondow. Exploration to obtain new prospect areas is still being carried out. Therefore, research on alteration and mineralisation characteristics is expected to be a reference for the discovery of new prospects. The research was conducted by identifying surface and subsurface data megascopically and microscopically. Microscopic observations with petrography and mineragraphy. To obtain surface data, alteration observations, channel sampling and grab sampling were carried out, while subsurface data were obtained from core drilling. The purpose of the study was to determine the alteration, mineralisation, oxidation, and deposits type. The study area has lithologies of hydrothermal breccia, diatreme breccia, fault breccia, and tuff breccia. Alteration developed in the form of vuggy sillica, massive sillica, advanced argillic, and argillic. Mineralisation includes gold and silver and sulphide minerals such as pyrite, chalcopyrite, sphalerite, enargite, covellite, and oxide minerals such as goethite, jarosite and hematite. The epithermal high sulphidation deposit type was formed at medium depth, with oxide-type ore.